Analysis and Simulation of Active Filters Using Operational Transconductance Amplifier (OTA) - Haitham K. Ali; Jihan S. Abdaljabar (European Scientific Journal, ESJ, 2017)
As the transistors are continuously scaling down, it becomes necessary to reduce voltage supply and power requirements of the circuit to increase its performance and stability. Whereas, current- mode devices require less number of stages with high output impedance results in improved performance and large bandwidth as compared to voltage-mode techniques. OTA are current-mode device that takes voltage as input and produces current as output with high gain and large bandwidth. The frequency bands were parameters were determined such as the cutoff frequency (fc), the band width (BW), the quality factor (Q), and the angular frequency (Wo). In this paper the design and the simulation of the transfer function has been done by using (MATLAB) in order to obtain the frequency response for all types of filter (the low pass filter, high pass filter, band pass filter and band stop filter).